Penegakan Hukum Terhadap Tindak Pidana Perjudian Online Di Wilayah Polda Sumatera Utara Tahun 2021 – 2024 - Sitorus, Sari Mahyuni; Panjaitan, Budi Sastra (JUNCTO: Jurnal Ilmiah Hukum, 2025)
This study aims to analyze law enforcement against online gambling crimes in the North Sumatra Regional Police area, as well as to identify the legal strategies implemented by the police in dealing with these crimes. In addition, this study also aims to examine the active participation of the North Sumatra Regional Police in efforts to prevent and eradicate online gambling through preventive measures, public education, and cross-sectoral cooperation. By using a normative legal approach and qualitative methods, this study is expected to provide a comprehensive picture of the dynamics of online gambling law enforcement and the challenges faced by the police during the 2021–2024 period. The method used is a normative legal approach with data collection techniques through interviews with police officers and review of relevant legal documents. The results of the study show that the North Sumatra Regional Police implement preventive, educational, and repressive strategies in a sustainable manner. These strategies include blocking gambling sites, cyber patrols, public education, and taking firm action against perpetrators. The challenges faced include limited cross-country digital regulations and the rampant promotion of online gambling on social media. Therefore, collaboration between agencies is key to tackling online gambling. Effective law enforcement is expected to provide protection and a sense of security to the community and reduce the number of digital crimes in the North Sumatra region.